Papillary Muscle Maneuvers: Pathophysiology-based Approach in Secondary Mitral Regurgitation - Evaldas Girdauskas; Sina Stock; Elisa Favot; Blerim Luani; Tatiana Sequeira-Gross; Christian Dumps; Maria von Stumm; Tamer Owais; Wolfgang von Scheidt (Reviews in Cardiovascular Medicine, 2024)
The treatment of secondary mitral regurgitation (SMR) remains challenging despite the implementation of modern heart failure medication and established catheter-based techniques. Only a subgroup of SMR patients benefit from mitral valve (MV) intervention, and the long-term prognostic benefit of different therapeutic approaches in SMR remains controversial. A literature search was conducted through PubMed and Embase databases to identify relevant studies addressing the pathophysiological background for papillary muscle maneuvers in SMR and currently available surgical techniques. Furthermore, the studies evaluating patients’ selection criteria for papillary muscle maneuvers were specifically considered. Articles were selected based on quality and relevance. Over the last two decades, papillary muscle maneuvers have evolved as a pathophysiology-based treatment strategy to address left ventricular (LV) remodeling in SMR. In particular, patients with severe leaflet tenting and moderate heart failure phenotype seem to benefit most from papillary muscle maneuvers that improve LV geometry and thereby the durability of MV repair. We conclude that papillary muscle maneuvers are an evolving pathophysiology-based treatment strategy of ventricular SMR which target papillary muscle displacement due to LV remodeling.